Li+ transport properties of sulfolane-based gel polymer electrolyte and effective suppression of lithium polysulfide dissolution in lithium–sulfur batteries. Issue 18 (16th August 2022) - Miyauchi, Hibiki; Inaba, Kohei; Takahashi, Keitaro; Arai, Nana; Umebayashi, Yasuhiro; Seki, Shiro
Abstract : New-type sulfolane gel electrolytes exhibited high battery performance owing to chemical and physical control of Li2 S n dissolution and diffusion properties. Abstract : Sulfolane (SL)-based gel polymer electrolytes composed of a polyether-based host polymer were investigated for long-lifecycle lithium–sulfur batteries. The proposed electrolytes were expected to cause chemical and physical suppression of Li2 S n dissolution and diffusion owing to the low Li2 S n solubility, derived from the highly concentrated SL-based electrolytes, and low Li2 S n diffusion, derived from the host polymer, respectively. The Li + transport properties, and Li + –SL and Li + –anion interactions, were analyzed by alternating current impedance measurements and Raman spectroscopy, respectively. The relationships between gel polymer electrolyte composition and Li + coordination structure/Li + transport properties were also investigated. The Li–S cells containing gel polymer electrolytes exhibited a sufficient discharge capacity in the first cycle (approx. 1150 mA h g −1 ) and stable charge discharge operation for 100 cycles. Application of the proposed electrolytes resulted in high battery performance owing to chemical and physical control of Li2 S n dissolution and diffusion, and favorable electrolyte/Li metal interface formation.